Esterification for butyl butyrate formation using Candida cylindracea lipase produced from palm oil mill effluent supplemented medium - Salihu, Aliyu; Alam, Md Zahangir; AbdulKarim, M. Ismail; Mohd. Salleh, Hamzah (Elsevier, 2014)
The ability of Candida cylindracea lipase produced using palm oil mill efﬂuent (POME) as a basal medium to catal yze the esteriﬁcation reaction for butyl butyrate formation was investi-gated. Butyric acid and n-butanol were used as substrates at different molar ratios. Different con-version yields were observed according to the afﬁnity of the produced lipase toward the substrates. The n -butanol to butyric acid molar ratio of 8 and lipase concentration of 75 U/mg gave the highest butyl butyrate formation of 63.33% based on the statistical optimization using face centered central composite design (FCCCD) after 12 h reaction. The esteriﬁcation potential of the POME based lipase when compared with the commercial lipase from the same strain using the optimum levels was found to show a similar pattern. It can be concluded therefore that the produced lipase pos-sesses appropriate characteristics to be used as a biocatalyst in the esteriﬁcation reactions for butyl butyrate formation